2001
DOI: 10.3109/03008200109014246
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Bone Sialoprotein, Osteopontin and Synthetic Polypeptides to Hydroxyapatite

Abstract: The phosphorylated acidic glycoproteins bone sialoprotein (BSP) and osteopontin (OPN) bind to hydroxyapatite (HA) crystals and may be involved in the regulation of bone mineralization. The HA-binding properties of these proteins have been attributed to glutamic acid-rich sequences in BSP and aspartic acid-rich sequences in OPN. The present study examines the roles of these polycarboxylate sequences in the binding of BSP and OPN to HA. Porcine BSP, OPN and the synthetic polypeptides poly-L-glutamic acid [Poly(G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 39 publications
3
122
0
1
Order By: Relevance
“…This notion is supported by HA binding studies, which have shown that BSP binds to HA, at least in part, via the contiguous poly[E] sequences. Synthetic homopolymers of poly[E], however, did not completely inhibit this binding (48). It was therefore suggested that additional domain(s), or specific conformational motifs on BSP, are involved in HA binding and perhaps in HA nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by HA binding studies, which have shown that BSP binds to HA, at least in part, via the contiguous poly[E] sequences. Synthetic homopolymers of poly[E], however, did not completely inhibit this binding (48). It was therefore suggested that additional domain(s), or specific conformational motifs on BSP, are involved in HA binding and perhaps in HA nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the adsorption characteristics of proteins or peptides to HAP or other calcium phosphate surfaces, primarily with a focus on understanding the mineralization induction or inhibition abilities of that particular protein. [7][8][9] Recently, Krout et al examined the influence that osteocalcin (OC) has on both the mineral structure and cell binding properties when it is included as a component of the mineralization solution. It was found that while there were no changes to the crystal properties, there was improved cellular adhesion to the samples through the incorporation of OC within the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological templated mineralization could be employed to synthesize bone mimetic materials. This process is thought to occur by binding the acidic groups of peptides with calcium ions and aligning them in an orientation that matches the crystal structure of HA (7). Studies have shown that a peptide motif could promote the nucleation and growth of HA crystals (8 -10).…”
mentioning
confidence: 99%